High Glucose Induced Upregulation of Cyclin a Associating with a Short Survival of Patients with Cholangiocarcinoma: A Potential Target for Treatment of Patients with Diabetes Mellitus. (28th May 2022) - Saengboonmee, Charupong; Detarya, Marutpong; Sangkhamanon, Sakkarn; Sawanyawisuth, Kanlayanee; Seubwai, Wunchana; Wongkham, Sopit
Abstract: Diabetes mellitus (DM) is associated with an increased risk and progression of cholangiocarcinoma (CCA). High glucose underlying the association between DM and CCA by modulating the intracellular signaling has been demonstrated. However, the effects of DM and hyperglycemia on cell cycle machineries and progression of CCA remain elucidated. CCA cells, KKU-213A and KKU-213B were cultured in normal (NG, 5.6 mM) or high glucose (HG, 25 mM) resembling euglycemia and hyperglycemia. Western blotting was used to determine expressions of cell cycle machineries in CCA cells. The expression of cyclin A in CCA tissues from patients with or without hyperglycemia was determined by immunohistochemistry. Pan-cyclin dependent kinases (CDKs) inhibitor and silencing of cyclin A expression were investigated as a possible modality targeting CCA treatment in patients with DM. High glucose induced expression of cell cycle machinery proteins in both CCA cells. Among these, cyclin A was consistently and significantly upregulated. Nuclear cyclin A was significantly increased in tumor tissues from CCA patients with hyperglycemia and was significantly associated with post-operative survival of shorter than 5 mo. Silencing cyclin A expression sensitized CCA cells to pan-CDKs inhibitor, suggesting the combined treatment as an alternative approach for treatment of CCA patients with DM.